State-NGO relations in the Mediterranean search and rescue operations: a review. (23rd March 2022) - Horii, Satoko
Since 2014, non-governmental organisations (NGOs) have been involved in migrant search and rescue (SAR) operations in the Mediterranean Sea. However, their efforts have not always been welcomed by the European Union (EU) and its member states, several of which have implemented regulations to interrupt such operations. Using a classification category developed in the literature, the present article explores the evolvement of the SAR NGO-state relations from the beginning of the Mediterranean migration crisis. It explains how the relations evolved from cooperative, co-optative to confrontational intentions. By examining these relationship patterns, the article argues that the relations are more nuanced than it looks. The significance of this paper is to critically assess the possible institutionalisation of non-governmental SAR operations into European border controls.